Television in Portugal (2000-2016): the curious case of Portuguese fiction - Merino, Francisco (Universidad de Chile. Instituto de la Comunicación e Imagen, 2017)
Portuguese television has always struggled with the country’s demography, geography and permeability to foreign contents. Until 2001, Portuguese television was unable to fulfil any of the Directives regarding minimum European production quotas, and one of its key features was the undisputed dominance of Brazilian telenovelas over Portuguese audiences. Today the situation has changed dramatically and the number of Portuguese telenovelas being broadcasted raised exponentially, as well as its ratings and share. In this article we will examine a very specific period, from 2000 to 2016, and study the dramatic fiction produced in Portugal during this timeframe. We will analyse Portuguese telenovela’s hegemony over prime-time, and the impact it is having on other television genres.